STUDENTS’ ENGLISH LANGUAGE EDUCATION STUDY PROGRAM PERCEPTION IN USING CANVA - Puspita Hasibuan; Nurhasanah Nurhasanah; Pinmade Vionita Tampubolon; Maisaro Maisaro; Muhammad Ikhwan (Jurnal Education and Development, 2026)
The students’ perception in using canva application on their presentation performance is the aim of this study. The informants of this study consisted of 20 students. The researcher used a purposive sampling technique to obtain subjects or informants. Data were obtained by distributing questionnaires and observations to informants. It was found that the results of student perceptions, eighth semester of the English Language Education Study Program, Institut Pendidikan Tapanuli Selatan is a positive category. The researcher found that the average score of the Strongly Disagree (1,25%), Disagree (18.75%), Neutral (32.75%) and Agree (41.5%), Strongly Agree (4.75%). Furthermore, the results of the students' presentation performance uses Canva application is positive category, the researcher found that the average score of the category is Very bad (1,25%), Not good (15%), Fairly good (56,75%), Good (12,25%) and Very good (6,25%) is categories Fairly Good.